ANALISIS KELAYAKAN INVESTASI PENGEMBANGAN USAHA ARTOMORO 2 DI MART DI GENTASARI - Septiana, Angga Merlinda; Darmawan, Akhmad (Media Ekonomi, 2015)
This research was aimed at knowing whether or not the the ARTOMORO2 Mart wasfeasible to be established on the market and marketing aspect, technical aspect of production and technology, management and human resources aspect, financial and economic aspect as well as the aspect of law and legality.The object of this research was an Analysis on the investment Expedience of BusinessDevelopment of Artomoro2 Mart. The analysis used were leasquare method, market share method, qualitative method or score load, S.W.O.T analysis method, Payback Period,Net present value, Internal Rate of Return, Profitability Index, and S.W.O.T Analysis of legal aspect. The result of this research showed that based on the market and marketing aspect, ARTOMORO2 Mart was feasible to be established because it was good in the competitive strategy. ARTOMORO2 Mart was also feasible accourding to the technical aspect of production and technology because it applied an advanced technology. The market did not produce commodities due to the fact that market was only selling. Based on the management and human resources aspect, ARTOMORO2 Mart was also feasible to be established because of the calculation of financial aspect showing that the investment was feasible to be established because of the calculation of financial aspect showing that the investment was feasible to be done. Based on the legal aspect analysis, ARTOMORO2 Mart was not feasible yet because it did not have a strong legal agency which was legitimized by the ministry of justice.Keyword : Market and Marketing Aspect, Technical Aspect of Production and Technology, Management and Human Resources and Aapect, Financial and Economic Aapect, Legal Aapect